Caracterização geofísica dos reservatórios do grupo Macaé no campo de Garoupa – Bacia de Campos - do Nascimento, Luana Fernandes [UNESP]; Vincentelli, Maria Gabriela Castillo [UNESP] (My University, 2015)
The study area is the Garoupa oil field which is offshore’s first important discovery of hydrocarbon production in carbonates in the Campos Basin. The high significance of carbonate rocks reservoirs for the global petroleum industry and its high complexity, combined with the fact that the Garoupa field be characterized as a mature field, make this research interesting to draw a present view of the area. The methodology used in this paper included well correlation techniques, petrophysical analysis and seismic interpretation (3D), in order to evaluate qualitatively and quantitatively the geophysical data’s response to the presence of carbonate rocks reservoirs. By analyzing the geophysical well profiles (gamma ray, resistivity, density and sonic) was possible to identify six reservoir levels in the Quissamã Formation calcarenites delimited by a structural-stratigraphic trap. The structural contour maps of the top of the Macae Group and two horizons that correspond to the reservoir levels were generated in time (ms) based on seismic interpretation. These maps show that the oil producing area of Garoupa field is a high structural located in the west side of the seismic cube interpreted, classified as a rollover limited by lateral faults that form a horst.
Geophysical characterization of the reservoirs of the Macaé group in the Garoupa field - Campos Basin